STUDI TENTANG PELAKSANAAN PEMBAGIAN WARISAN ATAS HARTA PUSAKO RANDAH DI KENAGARIAN LUBUK BASUNG DALAM LINGKUNGAN ADAT MINANGKABAU SUMATERA BARAT - Putri, Fika Yassha; Eddison, Ahmad; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the problem of inheritance distribution of pusako randah property in Lubuk Basung village which is in contrast to the collective inheritance distribution system for high pusako assets in the Minang indigenous community, whose inheritance rights are owned by heirs based on maternal or female lineage. In addition, it also contradicts the matrilineal kinship of the indigenous peoples in Minang where women are considered more dominant and are the successors of a family lineage. The formulation of the problem in this research is how is the implementation of inheritance distribution of pusako randah property in Lubuk Basung Kenagarian in the Minangkabau customary environment of West Sumatra. West. In processing the data the researchers used a qualitative method, the population in this study were some of the people in the Kenagarian Lubuk Basung with a sample that the researchers took was 5 people who were taken from traditional elders / ninik mamak and also community leaders in the Lubuk Basung Kanagarian. The data analysis technique used in this study is based on several opinions from respondents or using words. In qualitative data analysis, according to Miles and Huberman, it is carried out interactively through a process of data reduction, data presentation and conclusion drawing. The data collection techniques used are interview, observation, and documentation methods. Based on the results of research conducted by researchers in the field, the implementation of the distribution of the inheritance of the Minangkabau community tends to apply the Islamic heritage system but in practice the distribution is carried out on the basis of the principles of deliberation and consensus, where the distribution is carried out equally. This is because the community's soul likes to deliberate in determining a decision and in order to maintain family harmony so that there is no dispute or friction between the heirs.Key Words: Distribution Inheritance, Property Pusako Randah